2018
DOI: 10.1111/jfb.13675
|View full text |Cite
|
Sign up to set email alerts
|

Female‐biased dimorphism in size and age at maturity is reduced at higher latitudes in lake whitefish Coregonus clupeaformis

Abstract: Female-biased sexual dimorphism in size at maturity is a common pattern observed in freshwater fishes with indeterminate growth, yet can vary in magnitude among populations for reasons that are not well understood. According to sex-specific optimization models, female-biased sexual size dimorphism can evolve due to sexual selection favouring earlier maturation by males, even when sexes are otherwise similar in their growth and mortality regimes. The magnitude of sexual size dimorphism is expected to depend on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 36 publications
0
18
4
Order By: Relevance
“…In female graylings, the commonly observed female-biased dimorphism in size among other salmonid species (e.g. Tamate and Maekawa 2004;Morbey 2018) is not supported in our analysis, although length dimensions of the abdomen and distances between fins were generally longer in females. However, these differences may be a secondary effect of the position of the fins perhaps in relation to the extended dorsal and anal fin bases in males.…”
Section: Sexual Dimorphism In Graylingscontrasting
confidence: 85%
“…In female graylings, the commonly observed female-biased dimorphism in size among other salmonid species (e.g. Tamate and Maekawa 2004;Morbey 2018) is not supported in our analysis, although length dimensions of the abdomen and distances between fins were generally longer in females. However, these differences may be a secondary effect of the position of the fins perhaps in relation to the extended dorsal and anal fin bases in males.…”
Section: Sexual Dimorphism In Graylingscontrasting
confidence: 85%
“…Similarly, regarding item (ii), in over 80% of fish families where females and males look alike, it is the females that eventually reach larger sizes (Fig. 3B), even if this growth dimorphism can become attenuated in certain circumstances (81). This strong female dimorphism should lead to a rethink of the notion that the cost of reproduction causes growth to decline.…”
Section: Fish Growth Versus Reproductionmentioning
confidence: 94%
“…and DFBL, and this situation showed that head and fin length might differ by sex. Similarly, Morbey (2018) reported that sexual differences were generally seen in fin size and head morphology. It may occur because aquatic environments present different characteristics, habitats, or diets (Delariva & Agostinho, 2001).…”
Section: Charactersmentioning
confidence: 93%
“…Geographic and different environmental components can vary in single morphological characteristics, growth patterns, and body shape within and among populations (Firmat, Schliewen, Losseau, & Alibert, 2012). For fish, sexual dimorphism, generally, has been recorded in body size, fin size and shape, color pattern, and head morphology (Morbey, 2018). Females are usually larger than males of the same age, while males are larger than females for some species (Mann, 1980).…”
Section: Introductionmentioning
confidence: 99%